2020
DOI: 10.1186/s12940-020-00623-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ambient air pollution on glucose metabolism in Korean adults: a Korea National Health and Nutrition Examination Survey study

Abstract: Background: Exposure to air pollution was reported to affect glucose metabolism, increasing the risk of diabetes mellitus. We conducted an epidemiological study on glucose metabolism and air pollution by exploring the levels of fasting blood glucose (FBG) and hemoglobin A1c (HbA1c) with changes in ambient air quality, depending on the characteristics of the susceptible population. Methods: We carried out a cross-sectional analysis of a nationally representative sample of 10,014 adults (4267 in male and 5747 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 55 publications
5
15
0
4
Order By: Relevance
“…We found that the strongest effect estimates occurred at a time point of about five years. We also observed that FPG had a stronger effect estimate at earlier time points than HbA 1c , which is consistent with a previous study in which FPG showed a stronger association than HbA 1c in early exposure time windows [ 21 ]. HbA 1c represents the plasma glucose levels and effects thereon occurring within a few months of exposure, while FPG does the same within a much shorter time frame, e.g., a change in diet can decrease the plasma glucose level in a short period.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the strongest effect estimates occurred at a time point of about five years. We also observed that FPG had a stronger effect estimate at earlier time points than HbA 1c , which is consistent with a previous study in which FPG showed a stronger association than HbA 1c in early exposure time windows [ 21 ]. HbA 1c represents the plasma glucose levels and effects thereon occurring within a few months of exposure, while FPG does the same within a much shorter time frame, e.g., a change in diet can decrease the plasma glucose level in a short period.…”
Section: Discussionsupporting
confidence: 92%
“…Hwang and colleagues demonstrated that the sex-speci c effects could be explained by biological differences as well as differences in social exposures (Hwang et al, 2020). Generally, lung size, gas-blood barrier permeability and in ammation all vary by sex.…”
Section: Discussionmentioning
confidence: 99%
“…There are no specific air pollution data at the city or district level because of the limited number of air-quality monitoring stations. Thus, to estimate air pollution data of the administrative districts in Korea, we used a prediction model based on data from the Korean Air Quality Forecasting System (KAQFS) [ 13 ]. The KAQFS included the Sparse Matrix Operator Kernel Emissions version 2.7 and Community Multiscale Air Quality version 4.7.1, which used emission inventories, including the Multi-Resolution Emission Inventory for China, Regional Emission Inventory in Asia, and Clean Air Policy Support System [ 14 ].…”
Section: Methodsmentioning
confidence: 99%